2019
DOI: 10.1080/13887890.2018.1564074
|View full text |Cite
|
Sign up to set email alerts
|

Wing shape patterns among urban, suburban, and rural populations ofIschnura elegans(Odonata: Coenagrionidae)

Abstract: This is a repository copy of Wing shape patterns among urban, suburban, and rural populations of Ischnura elegans (Odonata: Coenagrionidae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Although sexual dimorphism is common in insects, including diving beetles (Bergsten et al, 2001; Bilton et al, 2008, 2016; Kiyokawa & Ikeda, 2022), we did not find different responses to urbanisation between males and females in the study species. Our result is in accordance with the findings of a damselfly study on I. elegans that exhibit strong sexual dimorphic differences but no different response to urbanisation in flight‐related traits between sex (Villalobos‐Jiménez & Hassall, 2019). However, other studies have found different responses to urbanisation occurring in the same traits between sex in some species of odonates (Tüzün et al, 2017) and carabids (Papp et al, 2020; Sukhodolskaya, 2013; Sukhodolskaya & Saveliev, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although sexual dimorphism is common in insects, including diving beetles (Bergsten et al, 2001; Bilton et al, 2008, 2016; Kiyokawa & Ikeda, 2022), we did not find different responses to urbanisation between males and females in the study species. Our result is in accordance with the findings of a damselfly study on I. elegans that exhibit strong sexual dimorphic differences but no different response to urbanisation in flight‐related traits between sex (Villalobos‐Jiménez & Hassall, 2019). However, other studies have found different responses to urbanisation occurring in the same traits between sex in some species of odonates (Tüzün et al, 2017) and carabids (Papp et al, 2020; Sukhodolskaya, 2013; Sukhodolskaya & Saveliev, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…For example, in ground beetles (Carabidae), urban individuals of Carabus violaceus have shorter elytron length than their non‐urban counterparts, whereas urbanisation has no effects on the elytron length of Abax parallelepipedus (Papp et al, 2020). In damselflies (Zygoptera), a significant difference was found in dispersal‐related traits of Coenagrion puella between urban and rural males (Tüzün et al, 2017) but not in Ischnura elegans in the same family Coenagrionidae (Villalobos‐Jiménez & Hassall, 2019). In our case, we think no responses in the flight‐related traits of I. ater may have resulted from the fact that it has long hind wings with a large area, compared with the other two species with similar body length (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since penguins have their modified remiges feathers greatly reduced (Livezey, 1989), wing bones area is a good estimative of the total wing area. The bone area was calculated from polygons formed by the landmarks placed on the bones perimeter (Villalobos‐Jiménez & Hassall, 2019). The landmarks used for each bone were, for the carpometacarpus landmarks 1−7, 12−17, and 22; for the caudal humerus landmarks 1, 3, 4, 8−16, and 20; for the ulna landmarks 1−3, 8−15, 17, and 18; for the radius 1−4, 11−16, and 19 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, they are sensitive to changes in water quality to meet the needs of the larvae, as well as changes in terrestrial vegetation and landscape structure to meet the perching and foraging requirements of adults (Corbet, 1999). Dragonflies are also a good indicator taxon in river and wetland systems as they are sensitive to many abiotic and biotic stressors, such as physical and chemical parameters of water (Villalobos‐Jiménez et al., 2016, 2019; Simon et al., 2019). Earlier studies demonstrated that the occurrence and/or abundance of damselflies was positively correlated with environmental integrity and negatively correlated with their contrasting ecophysiological requirements (Monteiro‐Junior et al., 2014).…”
Section: Introductionmentioning
confidence: 99%